Analysis of Sealing Performance and Mechanism of Biomimetic Superoleophobic Surface Structure - Q. Li; S. Cheng; Z. Hou; W. Zhao; Q. Guan (Journal of Applied Fluid Mechanics)
Sealing performance is critical for mechanical components, particularly in automotive engines, where oil leaks remain a persistent challenge. This paper presents the design of novel biomimetic sealing surfaces that replicate the structural characteristics of biological surfaces with superhydrophobic and superoleophobic properties. A comprehensive evaluation of the design and performance of these biomimetic surfaces is provided. A multilayer microarray structure was designed using multivariate coupled mimetic theory. The structure consists of a smooth surface, a primary biomimetic weave surface, and a secondary biomimetic weave surface. Biomimetic superoleophobic surfaces of varying grades were fabricated on automobile engine gaskets through machining. This paper analyzes the dispersion of oil droplets, impact dynamics, and contact time between different surface structures using Volume of Fluid (VOF), Coupled Level Set and Liquid Volume (CLSVOF), and Computational Fluid Dynamics (CFD). The results demonstrate that the biomimetic textured surface significantly enhances oleophobicity by minimizing contact with oil droplets, reducing the maximum diffusion diameter by approximately 15% compared to a smooth surface. The interaction duration of oil droplets on the biomimetic surface is reduced by 14.7%, leading to improved sealing efficiency. This study indicates that finely structured biomimetic surfaces have promising applications in automotive sealing technology. Further miniaturization and optimization of these structures are expected to enhance sealing efficiency, particularly in demanding industrial environments.